The Musyrif Guidance Program In Boarding School At Middle School - Aldi Muhammad Thoha; Imas Kania Rahman; Ibdalsyah Ibdalsyah (Prophetic guidance and counseling journal, 2020)
The management of the boarding school counseling program at the middle level that is not organized and structured will impact on students, including those who are not at home in the dormitory, commit violations, and do not have Islamic customs. this is caused by the lack of responsibility of a musyrif in managing students in the dormitory, this requires maximum assistance and good services in the form of providing guidance programs in producing professional and responsible musyrif. This research aims to find out the best musyrif guidance program in secondary level boarding schools. The approach used in this research is descriptive qualitative By using the method of field research, data collection techniques carried out were observation, interviews, open questionnaires, and documents. The formulation of musyrif and musyrifah guidance programs in Boarding School secondary schools was validated through focus group discussions (FGD) involving four experts namely guidance and counseling experts, Islamic religious experts, caretakers of Islamic boarding schools, and linguists. The results of this study indicate that the musyrif and musyrifah guidance programs at boarding schools at the secondary level are arranged based on program components, such as basic services, responsive services, individual planning, and system support. The guidance material consists of leadership, manners, achievement motivation, decision-making skills, diversity of characters and cultures, parenting, and responsibilities.AbstrakPengelolaan program bimbingan musyrif dan musyrifah boarding school ditingkat menengah yang tidak terorganisir dan terstruktur akan berimbas pada peserta didik diantaranya tidak betah di asrama, melakukan pelanggaran, dan tidak memiliki adab Islami. Hal ini menuntut adanya pendampingan maksimal dan layanan yang baik berupa pembekalan program bimbingan dalam menghasilkan musyrif dan musyrifah yang profesional dan bertanggungjawab. . Hal ini disebabkan karena kurangnya tanggung jawab. Penelitian ini bertujuan untuk mengetahui program bimbingan musyrif terbaik di pesantren tingkat menengah. Pendekatan yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Dengan menggunakan metode penelitian lapangan, teknik pengumpulan data yang dilakukan adalah observasi, wawancara, angket terbuka dan dokumen. Penyusunan program bimbingan musyrif dan musyrifah di sekolah menengah Pesantren divalidasi melalui FGD yang melibatkan empat orang ahli yaitu ahli bimbingan dan konseling, ahli agama Islam, pengurus pondok pesantren, dan ahli bahasa. Hasil penelitian ini menunjukkan bahwa program bimbingan musyrif dan musyrifah di pesantren tingkat menengah disusun berdasarkan komponen program, seperti pelayanan dasar, pelayanan reponif, perencanaan individu dan dukungan sistem. Materi bimbingan terdiri dari kepemimpinan, budi pekerti, motivasi berprestasi, keterampilan mengambil keputusan, keragaman karakter dan budaya, pola asuh dan tanggung jawab.